'Mostly accurate with occasional piles of bullshit': patient 'boundary-work' in an online scientific controversy. Issue 3 (2nd September 2019) - Phillips, Tarryn
ABSTRACT: People with contested illnesses such as Gulf War Syndrome and multiple chemical sensitivities (MCS) have struggled to have their claims to chemical injury recognised as scientifically valid. Patients have thus built on shared experiences and formed 'embodied health movements', to challenge mainstream scientific understandings of toxicity and disease causality. Digital technologies have changed the scale and scope of patient sharing and collaboration, yet little attention has been paid to how patients govern each others' scientific claims. This paper draws from an online qualitative survey of forum users with self-reported MCS ( N  = 186) to investigate how patient groups internally debate scientificity – in this case over a controversial new 'neural retraining' treatment. Despite their own scientific marginalisation, MCS patients conducted 'boundary-work' to demarcate scientifically legitimate claims from 'pseudo-science' in their analysis of peer theories, and used scientific criteria as a powerful tool to claim and dispute epistemic authority. Moreover, this inter-patient boundary-work had profound social and therapeutic implications in the movement, particularly with respect to the politics of recognition, community solidarity and peer support.